Integrating soil and crop metrics with precision agriculture: Pusa N Doctor app for sustainable nitrogen management in maize - Sayantika Sarkar; Pravin Kumar Upadhyay; Abir Dey; Utpal Ekka; Sanjay Singh Rathore; Kapila Shekhawat; Md. Yeasin; Rajiv Kumar Singh; Subhash Babu; Anchal Dass; Tarik Mitran; Navin Kumar Sharma; et al. (PLoS ONE, 2025)
Efficient nitrogen (N) management is critical for sustaining high maize yields while minimizing environmental impacts, as conventional practices often lead to N losses, greenhouse gas emissions, and reduced eco-efficiency. To address these challenges, the “Pusa N Doctor” app was developed using dark green colour index (DGCI) for precision N management in maize. The app was further validated in experiment conducted with three N rates- 0 kg/ha (N0PK), 50 kg/ha (N0PK), and 75 kg/ha (N75PK) as basal, along with two splits of N at 35 and 45 DAS as per app (N50PK+App and N75PK+App) and GSTM (N50PK + GSTM and N75PK+GSTM). The plant height, leaf area index, and plant N concentration was highest in N75PK+App. The highest crop growth rate between 0-30 DAS was observed in the N75PK+App treatment (9.97 g/m²/day). Conversely, the maximum relative growth rate between 30-60 DAS was in the N50PK+App, while the lowest was in N75PK+App. The highest harvest index of 35.13% was in N50PK+App. Except for N75PK+App and recommended dose of fertilizer (RDF), the partial N balance was close to 1, with a minimum value of 0.87 in N75PK+App. The lowest virtual N was in N50PK+App (0.45), while in N75PK+App it was 2.16 times higher than RDF. All N fertilized treatments except N50PK+App witnessed increased cost of cultivation over RDF. N50PK+App had 29.5% lower GHGI of N2O, with 11.6% and 13.3% higher energy and GHG-based eco-efficiency respectively than RDF. Thus, applying 50 kg N as basal along with its 2 splitting as per Pusa N Doctor, optimizes maize-growth, N use efficiency, eco-efficiency, and reduces GHG emissions.